ALUR PELAYANAN PENDAFTARAN RAWAT JALAN DI PUSKSEMAS SEI PANAS - Nafisa, Frasya Amanda; Safitri, Nur Indah; Hasanah, Sinta Niswatun; Anisa, Desfa (LPPM Universitas Awal Bros, 2025)
Service activities begin with the patient registration process through the e-Queue machine and the Outpatient Registration Area (TPPRJ). The patient registration procedure in the outpatient department is divided into new and existing patients. A structured procedure can reduce potential delays in the registration process, thereby speeding up the service flow and increasing patient satisfaction. The outpatient registration process at the Sei Panas Community Health Center has been running according to established procedures, with the e-Queue system simplifying patient registration. However, observations at the Sei Panas Community Health Center indicate that some patients do not bring their identification, thus causing obstacles in the outpatient registration process. This will impact the ineffectiveness of outpatient registration services at the Sei Panas Community Health Center. Some of these obstacles include patients who do not bring their identification (KTP / KK / BPJS / KIA) when registering for treatment. Due to these obstacles, we conducted outreach to patients to bring their identification before coming to the health center. This will not hinder staff in carrying out the registration process.